2014
DOI: 10.4171/ggd/244
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of locally compact groups of polynomial growth and shape of large balls

Abstract: Abstract. We show that any locally compact group G with polynomial growth is weakly commensurable to some simply connected solvable Lie group S, the Lie shadow of G. We then study the shape of large balls and show, generalizing work of P. Pansu, that after a suitable renormalization, they converge to a limiting compact set, which is isometric to the unit ball for a left-invariant subFinsler metric on the so-called graded nilshadow of S. As by-products, we obtain asymptotics for the volume of large balls, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 30 publications
0
79
0
Order By: Relevance
“…Besides Bass' volume growth estimate (1.1), Pansu [42] proved a more delicate volume growth property for groups of polynomial volume growth (see also Breuillard [5]). He showed that for the Cayley graph (G, S) of a group G of polynomial volume growth the following limit exists 6) where D ∈ N. Then it is easy to see (Lemma 2.1) that for any θ ≪ 1, there exists R 0 (θ, S) such that…”
Section: Introductionmentioning
confidence: 91%
“…Besides Bass' volume growth estimate (1.1), Pansu [42] proved a more delicate volume growth property for groups of polynomial volume growth (see also Breuillard [5]). He showed that for the Cayley graph (G, S) of a group G of polynomial volume growth the following limit exists 6) where D ∈ N. Then it is easy to see (Lemma 2.1) that for any θ ≪ 1, there exists R 0 (θ, S) such that…”
Section: Introductionmentioning
confidence: 91%
“…This follows from the Baker-Campbell-Hausdorff formula (cf. §3.3 and the proof of Lemma 5.5 in [6]). …”
Section: The Carnot Group As the Asymptotic Conementioning
confidence: 88%
“…For instance, we can say that a group element w ∈ Z 2 has a simple spelling if w = av i + bv i+1 for consecutive significant generators. We can verify that every word has a simple spelling with respect to the standard generators, whereas only 1 in 36 elements has a simple spelling in S = ±{6e 1 , e 1 , 6e 2 This does depend on the generating set-only on the convex hull, as usual, but not only on its area-and it holds uniformly at large word-lengths n, as well as when averaging over words of length ≤ n. As a check, recall that Pick's theorem says that A = i + b/2 − 1. We know that r ≤ b and i ≥ 1, which means r/2A ≤ 1, which is required for plausibility.…”
Section: Asymptotic Densitymentioning
confidence: 94%
“…As a consequence, the spheres in the word metric, once normalized, converge to a limit shape. This is a small special case of the theory for finitely-generated nilpotent groups and, more generally, lattices in Lie groups of polynomial growth (see Pansu and Breuillard [9,2]). Here we give an elementary proof in terms of the combinatorial group theory and Euclidean geometry.…”
Section: The Limit Metricmentioning
confidence: 99%